Negative electrode of solid-state battery and solid-state battery

By setting a specific hole structure on the negative electrode current collector of the solid-state battery, the precipitation problem of metal lithium and the like during repeated charging and discharging is solved, and the battery life is extended and the high energy density is maintained.

CN119725361APending Publication Date: 2025-03-28HONDA MOTOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411036304.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-07-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the existing solid-state batteries are repeatedly charged and discharged, they are prone to precipitation of metal lithium, increase resistance, and even cause internal short circuits of the positive and negative electrodes, reducing battery life.

Method used

A metal porous body is used as the negative electrode current collector, and a pore portion without a metal porous body is provided on the surface along the thickness direction, with a pore diameter of 100 μm to 180 μm, and the proportion of the total volume of the pore portion with respect to the void ratio of the metal porous body is 10vol% or less to suppress the precipitation of metal lithium or the like.

Benefits of technology

It effectively improves the filling density of electrode active substances, inhibits the precipitation of metal lithium, etc., extends the battery life, and maintains high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725361A_ABST
    Figure CN119725361A_ABST
Patent Text Reader

Abstract

Provided is a negative electrode for a solid-state battery, the negative electrode having a large filling amount of an electrode active material and being less susceptible to an internal short circuit or the like caused by the deposition of metallic lithium even in the case of repeated charging and discharging. By providing the negative electrode of the solid-state battery, the energy efficiency of the solid-state battery can be further improved. The present invention relates to a negative electrode for a solid-state battery, the negative electrode being provided with: a negative electrode current collector having a metal porous body as a constituent material; and a negative electrode active material filled in the negative electrode current collector, in which pores having no metal porous body are provided in the thickness direction from the surface on the solid electrolyte side of the negative electrode current collector, the pore diameter of the pores is 100-180 [mu] m, and the depth in the thickness direction is greater than the pore diameter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode of a solid-state battery and a solid-state battery. Background Art

[0002] In recent years, in order to ensure that more people can use appropriate, reliable, sustainable and advanced energy, research and development of solid-state batteries that contribute to energy efficiency are being carried out. Solid-state batteries have high energy density and are used for a wide range of purposes. In particular, lithium-ion secondary batteries that can be rapidly charged and discharged are also of great importance as a sustainable and advanced energy source for electric vehicles (EVs), hybrid electric vehicles (HEVs), etc.

[0003] As a structure of a solid-state battery, it is known that the current collector constituting the negative electrode is a foam metal in order to increase the packing density of the electrode active material. Patent Document 1 discloses a semi-solid-state battery, in which a porous covering layer is arranged on the electrode layer as a semi-solid-state battery with a foam metal as a current collector. The porous covering layer in Patent Document 1 can absorb and collect the electrolyte squeezed out from the electrode layer even when the negative electrode active material expands during charging of the semi-solid-state battery, and can suppress the reduction in capacity caused by the reduction of the electrolyte and repeated charging and discharging. Prior art literature Patent Literature

[0004] Patent Document 1: Japanese Patent No. 7008737 Summary of the invention Technical problem to be solved by the invention

[0005] In order to contribute to further energy efficiency, solid-state batteries are also required to maintain battery life under repeated charge and discharge. As required characteristics for this purpose, for example, when the solid-state battery is repeatedly charged and discharged, lithium ions, sodium ions, etc. accept electrons at the negative electrode and metal lithium, metal sodium, etc. are precipitated at the negative electrode. If metal lithium, etc. are precipitated at the negative electrode, sometimes the resistance of the solid-state battery increases due to the easy generation of gaps between the layers, and internal short circuits between the positive and negative electrodes may also occur. In particular, in high-capacity negative electrodes, the precipitation of the metal lithium, etc. is prone to occur.

[0006] In this context, the present invention provides a negative electrode, which, when used as a solid-state battery, makes the filling density of the electrode active material above a prescribed level and is less likely to produce the effects of precipitation of metal lithium, etc., such as internal short circuits. Moreover, by providing the negative electrode of the solid-state battery, it is helpful to further improve the energy efficiency of the solid-state battery. Technical solutions for solving technical problems

[0007] In order to achieve the above object, the present invention provides the following technical solutions. [1] A negative electrode of a solid-state battery, which is a negative electrode of a solid-state battery, comprising: a negative electrode collector, which uses a metal porous body as a constituent material; and a negative electrode active material filled in the above-mentioned negative electrode collector, wherein the above-mentioned negative electrode collector is provided with a pore portion that does not have the metal porous body along the thickness direction from the surface of the solid electrolyte side, and the pore size of the above-mentioned pore portion is 100μm to 180μm.

[0008] In the case where metal lithium or the like is precipitated at the negative electrode of [1], the precipitation of metal lithium or the like tends to occur concentratedly inside the pores, and the precipitation of metal lithium or the like to the negative electrode interface or the like is easily suppressed. Therefore, when the negative electrode of [1] is used as a solid-state battery, the amount of negative electrode active material per unit area of ​​the negative electrode is made to be above a prescribed value, and the battery life is unlikely to be reduced even if charge and discharge are repeated.

[0009] [2] The negative electrode of a solid-state battery according to [1], wherein the ratio of the total volume of the pores to the porosity of the metal porous body (total volume of the pores / porosity) is 10 vol% or less.

[0010] The negative electrode whose total volume ratio of the pore portion is within the above range is easy to maintain a high energy density as a solid-state battery. If the total volume ratio of the pore portion is too large, it is difficult to maintain a high amount of negative electrode active material, and there is a tendency for energy density to decrease. This is because the capacity of the pore portion is too much compared to the volume of the metal lithium precipitated by charging, and it is difficult to maintain the height of the energy density brought by the filling of the negative electrode active material into the metal porous body.

[0011] [3] A negative electrode for a solid-state battery according to [1] or [2], wherein the ratio of the total volume of the pores to the porosity of the metal porous body (total volume of the pores / porosity) is 8 vol% or less.

[0012] Solid-state batteries with a negative electrode of [3] are more likely to maintain a higher energy density. Figure 3 As shown, according to the present inventors, if the ratio of the total volume of the pores to the porosity is 8 vol % or less, the decrease in energy density can be more reliably suppressed.

[0013] [4] The negative electrode of a solid-state battery according to any one of [1] to [3], wherein the depth of the pores in the thickness direction is 3 μm or more.

[0014] When the hole portion has the above depth or more, it tends to be easy to reliably secure a deposition space for metal lithium or the like during charge deposition, and the solid-state battery with high energy density is likely to be obtained.

[0015] [5] The negative electrode of a solid-state battery according to any one of [1] to [4], wherein the depth of the pores in the thickness direction is 5 μm or more.

[0016] When the hole portion has the above depth or more, it tends to be easier to more reliably secure the deposition space for lithium or the like when metal lithium or the like is charged and deposited, and it is easier to achieve a solid-state battery with higher energy density.

[0017] [6] The negative electrode of a solid-state battery according to any one of [1] to [5], wherein the hole is a through hole.

[0018] If the pores are through holes, lithium ions and the like tend to be easily and uniformly supplied to the pores, and metal lithium and the like are stably deposited in the pores, so that the cycle characteristics tend to be more easily maintained.

[0019] [7] The negative electrode of a solid-state battery according to any one of [1] to [6], wherein the cross-sectional shape of the hole is circular or quadrilateral.

[0020] If the cross-sectional shape of the hole portion is circular, metal lithium and the like are easily and stably precipitated in the hole portion. In addition, if the cross-sectional shape of the hole portion is quadrilateral, the specific surface area per unit volume of the hole portion becomes larger. Therefore, for example, during rapid charging, it is easy to stably form the initial precipitation of metal lithium and the like in the hole portion.

[0021] [8] The negative electrode of a solid-state battery according to any one of [1] to [7], wherein the negative electrode active material is a silicon-based material.

[0022] The above-mentioned negative electrode is preferably used when the negative electrode active material is a silicon-based material.

[0023] [9] A solid-state battery comprising the negative electrode described in any one of [1] to [8]. Effects of the Invention

[0024] According to the solid-state battery including the above negative electrode, the packing density of the electrode active material can be set to a predetermined value or higher, and a reduction in battery life due to the precipitation of metal lithium or the like can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is an image diagram showing the negative electrode and the solid electrolyte of the solid-state battery in this embodiment. Figure 2 The negative electrode in this embodiment will Figure 1 FIG. 1 is an image diagram showing an enlarged portion of the image. Figure 3 This is a graph showing the value of energy density relative to the capacity of the negative electrode active material. DETAILED DESCRIPTION

[0026] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0027] [Negative electrode of solid-state battery] The negative electrode of the solid-state battery of this embodiment comprises a negative electrode current collector made of a metal porous body and a negative electrode active material filled in the negative electrode current collector. A hole portion is provided on the surface of the negative electrode current collector along the thickness direction from the solid electrolyte side, the hole portion does not have a metal porous body, and the pore diameter of the hole portion is 100 μm to 180 μm.

[0028] The negative electrode of this embodiment is used for a solid-state battery having a structure in which a solid electrolyte is filled between the positive electrode and the negative electrode. It is known that solid-state batteries have advantages such as low risk of fire, rapid charging, difficulty in deterioration, and long life. The structure of the solid-state battery is not particularly limited, and can be any structure such as a cylindrical, square winding type, a laminated stacked type, etc.

[0029] Even when the negative electrode of the present embodiment is used in a solid-state battery, it is difficult to produce a reduction in battery life caused by repeated charging and discharging. In this regard, according to the following reasons, compared with a secondary battery in which the electrolyte is a liquid, a short circuit phenomenon in the case of metal lithium and the like precipitating at the negative electrode is prone to occur in a solid-state battery. In contrast, the negative electrode of the present embodiment easily suppresses the precipitation of metal lithium and the like to the negative electrode interface, so even if it is a solid-state battery, the battery life is difficult to reduce.

[0030] It can be considered that in solid-state batteries, the occurrence of short circuit phenomena in the case of precipitation of metallic lithium, etc. at the interface of the negative electrode, etc., is caused by the following reasons, etc. In solid-state batteries, the negative electrode and the solid electrolyte layer form an interface between the solids. In the case of precipitation of metallic lithium, it is difficult for lithium ions to conduct at the interface between the negative electrode and the solid electrolyte at the precipitation site, and the resistance is also easily increased. As a result, cracks are easily generated in the electrode or the solid electrolyte layer, making it difficult to function as a battery, and the precipitated metallic lithium invades the gap of the solid electrolyte layer, which is likely to cause a short circuit phenomenon. On the other hand, in a secondary battery whose electrolyte is liquid, even if cracks occur in the electrode, the liquid electrolyte will penetrate into the cracks and maintain the conduction of lithium ions, etc. In addition, even if metallic lithium, etc., is precipitated between the electrode and the separator, a short circuit will not occur until the separator breaks, so the time before short circuit is also longer than that of a solid-state battery.

[0031] In addition, the solid-state battery with the negative electrode of the present embodiment is suitable for lithium-ion secondary batteries with positive electrodes, negative electrodes, solid electrolytes and other battery elements as needed. Lithium-ion secondary batteries can be applied to a wide range of uses such as mobile devices such as mobile phones and notebook computers, and in-vehicle use. As long as the lithium-ion secondary battery has the structure of the present embodiment as the negative electrode. The structure other than the negative electrode can directly adopt the battery elements of the known lithium-ion secondary battery. The structure of the lithium-ion secondary battery can include, for example, a lithium-ion secondary battery formed by stacking the negative electrode of the present embodiment, the positive electrode facing the negative electrode, and the solid electrolyte layer between the positive electrode and the negative electrode.

[0032] (Negative electrode current collector) The negative electrode current collector is formed with a metal porous body as a constituent material. The metal porous body is not particularly limited as long as it is a metal material having porous spaces generated by foaming. The metal constituting the metal porous body may be, for example, nickel, nickel-chromium alloy, aluminum, stainless steel, titanium, copper, silver, etc., preferably copper or stainless steel.

[0033] The negative electrode current collector formed of a metal porous body has a large surface area. The surface area of ​​the negative electrode current collector is not particularly limited, but is preferably 1000 m 2 / m 3 ~6000m 2 / m 3 . Therefore, the negative electrode current collector can increase the amount of active material per unit area of ​​the electrode layer by filling the electrode mixture containing the negative electrode active material. Therefore, the negative electrode of this embodiment has a high energy density when used as a solid-state battery. In addition, if the negative electrode current collector is a metal porous body, it is easy to form a thick film active material layer even if the electrode mixture is not thickened. Therefore, the negative electrode of this embodiment can easily achieve high capacity when used as a solid-state battery.

[0034] The negative electrode current collector is provided with holes. Figure 1 and Figure 2 The image diagram of the negative electrode current collector is used to illustrate the pores. Figure 1 In the embodiment, the negative electrode 1 is filled with a negative electrode active material 23 on the negative electrode collector 21. The negative electrode collector 21 is provided with a hole portion 22 along the thickness direction W from the surface of the solid electrolyte 31 side. The hole portion 22 does not have a metal porous body constituting the negative electrode collector 21, that is, the hole portion 22 is a space (void) without a skeleton of the metal porous body. It should be noted that when the hole portion 22 is used as a solid-state battery, a precipitate of metallic lithium may exist inside.

[0035] The reason why the negative electrode having the negative electrode collector having the above-mentioned pore portion becomes a negative electrode with high energy density as a solid-state battery is as follows. When repeatedly charged and discharged as a solid-state battery, the lithium ions and electrons present near the negative electrode are easily transferred to the inside of the pore portion along the metal skeleton and solid electrolyte particles of the negative electrode collector. The lithium ions are easily and stably precipitated as metallic lithium inside the pore portion. Compared with the previous solid-state batteries in which metallic lithium is precipitated at random positions of the negative electrode, such a solid-state battery can control the precipitation position of lithium. Therefore, the internal short circuit caused by the precipitation of metallic lithium in the previous solid-state batteries is suppressed, and the cycle characteristics are high.

[0036] The pore diameter R is 100 μm to 180 μm, preferably 120 μm to 180 μm. If the pore diameter R is too small, in order to maintain the space for the precipitation of metallic lithium, it is necessary to increase the number of pores, and the strength of the negative electrode collector is easily reduced. If the pore diameter R is too large, the surface area of ​​the metal porous body becomes smaller, and it is difficult to maintain the height of the energy density. In addition, when the shape of the cross section (cross-sectional shape) of the pore portion in the horizontal direction orthogonal to the thickness direction W (hereinafter referred to as the "horizontal direction") is circular, the pore diameter R is the diameter (inner diameter) of the circle, and when the cross-sectional shape is a quadrilateral, the pore diameter R is the diameter of the inscribed circle. The pore diameter R in this embodiment refers to the average value calculated based on the image of the extracted pore portion obtained by binarizing the surface of the solid electrolyte side of the negative electrode collector with an electron microscope at a magnification of 50 times.

[0037] The cross-sectional area of ​​the hole 22 in the horizontal direction is preferably 6.0×10 -5 cm 2 ~3.0×10 -4 cm 2 If the cross-sectional area is too small, it is difficult to properly cause the metal lithium to precipitate into the pores 22 , and if the cross-sectional area is too large, it is difficult to maintain a high energy density as a solid-state battery.

[0038] The hole portion 22 preferably has a depth H in the thickness direction W that is greater than the hole diameter R (see Figure 2 ). The depth H is the length from the surface of the solid electrolyte side of the negative electrode collector 21 to the end inside the hole portion 22 (when the hole portion 22 is a through hole, it is the same as the film thickness of the metal porous body in the thickness direction W). When the depth H of the hole portion 22 is larger than the pore diameter R, it becomes a negative electrode in which metallic lithium is easily and stably precipitated inside the hole portion while ensuring a sufficient filling amount of the negative electrode active material 23. In addition, from the viewpoint of being able to ensure sufficient capacity for the precipitation of metallic lithium inside the hole portion 22, the depth H of the hole portion 22 in the thickness direction W is preferably 3 μm or more, and particularly preferably 5 μm or more.

[0039] The number of holes 22 provided in the negative electrode current collector is not particularly limited. From the viewpoint of easily ensuring sufficient capacity for the precipitation of metallic lithium inside the holes 22, the number of holes is preferably 2 (holes / cm2) relative to the surface area of ​​the negative electrode current collector 21. 2 ) or more, more preferably 5 (pieces / cm 2 ) or more. In addition, from the viewpoint of easily maintaining the strength of the negative electrode current collector, the number of pores is preferably 10 (pores / cm) relative to the surface area of ​​the negative electrode current collector 21. 2 ) or less, more preferably 9 (pieces / cm 2 )the following.

[0040] As described above, the pore portion 22 preferably has an internal volume that can fully precipitate metallic lithium. On the other hand, if the internal volume of the pore portion 22 is excessive, useless space where metallic lithium is not precipitated will be maintained. In this case, the negative electrode has a tendency to be difficult to maintain the filling amount of the negative electrode active material and to maintain a high energy density as a solid-state battery. In this regard, when the negative electrode of the present embodiment is used as a solid-state battery, the amount of metallic lithium precipitated in the negative electrode collector 21 varies according to the structure of the battery, the current value during charging, etc. If the changes caused by the structure of such a solid-state battery are taken into account, it is preferred that the pore diameter R of the pore portion 22 is less than 2L (R≤2L) relative to the growth rate L (μm / h) of lithium when charged at 1C. The negative electrode 1 obtained by providing the negative electrode collector 21 with a pore diameter R within the above range can become a negative electrode with high energy density that can cope with rapid charging and high output as a solid-state battery. The growth rate L of lithium when charged at 1C is calculated by charging at a constant current at 1C until a specified capacity of 3mAh / cm 2 The growth amount of lithium deposited at 1000 Å is converted into a value per hour. The pore diameter R in the present embodiment is preferably determined based on a lithium growth rate L of 50 μm / h to 90 μm / h.

[0041] The ratio of the total volume of the above-mentioned pore portion to the porosity of the above-mentioned metal porous body (total volume of the pore portion / porosity) is preferably 10 vol% or less, particularly preferably 8 vol% or less. The total volume of the pore portion 22 can be said to be a space for the precipitation of metallic lithium. Therefore, if the ratio of the total volume of the pore portion 22 to the porosity of the metal porous body is within the above range, it is easy to maintain a higher energy density as a solid-state battery. The lower limit of the above ratio is not limited. From the perspective of easily ensuring the precipitation space of metallic lithium, it is preferably 1 vol% or more, particularly preferably 5 vol% or more. The porosity (porosity) of the negative electrode collector 21 can be measured by gas adsorption or mercury injection. The total volume of the pore portion is obtained by multiplying the volume of each pore portion by the number of pores. The volume of each pore portion can be calculated by the depth and cross-sectional area measured by observing the pore portion cut in the horizontal direction using an argon beam or the like with an electron microscope, or by the measured depth, cross-sectional shape and pore size.

[0042] When the precipitation of metallic lithium relative to the pore portion 22 proceeds uniformly relative to the internal surface of the pore portion 22, the metallic lithium grows stably compared to when the precipitation proceeds unevenly according to the location, and it is easy to maintain the cycle characteristics as a solid-state battery. From the viewpoint of uniform precipitation of such metallic lithium relative to the pore portion 22, the pore portion 22 is preferably a through hole. If the pore portion 22 is a through hole, lithium ions easily invade the pore portion 22 uniformly from the upper and lower directions of the pore portion 22. Therefore, compared with the pore portion 22 having a bottom surface, metallic lithium is more likely to be stably and uniformly precipitated.

[0043] In addition, the cross-sectional shape of the hole portion 22 (the shape in the horizontal direction when the hole portion 22 is observed from the solid electrolyte side) is not particularly limited, and may be circular, elliptical, quadrilateral, polygonal, star-shaped, etc. The cross-sectional shape of the hole portion 22 is preferably circular or quadrilateral. In the case where the cross-sectional shape is circular, lithium is easily precipitated uniformly relative to the hole portion 22, and it is easy to maintain the cycle characteristics as a solid-state battery. If the cross-sectional shape of the hole portion 22 is a quadrilateral, the specific surface area inside the hole portion 22 can be increased. Therefore, in the case of rapid charging, etc. as a solid-state battery, the initial lithium precipitation is easy to proceed. It should be noted that, in the case of an elliptical cross-sectional shape, the aperture is the arithmetic mean of the major diameter and the minor diameter, in the case of a polygon, the aperture is the diameter of the inscribed circle, and in the case of a star, the aperture is the diameter of the circumscribed circle.

[0044] (Negative electrode active material) The negative electrode active material 23 is not particularly limited, and a battery element of a known solid-state battery can be used. As the negative electrode active material 23, for example, silicon-based materials, carbon-based materials, metal-based materials, etc. can be cited. The negative electrode 1 of the present embodiment is suitable for use in the case where the negative electrode active material 23 is a high-capacity silicon-based material. Here, in the case of using a silicon-based material as the negative electrode active material 23, if it is repeatedly charged and discharged as a solid-state battery, silicon is prone to expansion and contraction. Therefore, there is a tendency for the negative electrode active material 23 to easily slip from the negative electrode collector 21, the interface becomes unstable, and the precipitation of metallic lithium is easily accelerated. On the other hand, in the case of using the negative electrode active material 23 of the silicon-based material in the negative electrode 1 of the present embodiment, metallic lithium is also easy to stably precipitate relative to the pore portion 22. In addition, since the negative electrode collector 21 is a metal porous body, it is also difficult for the negative electrode active material 23 to slip.

[0045] The negative electrode active material 23 may include SiOx (0<x<2), Si-C, a composite material of silicon and carbon, etc. as silicon-based materials. Carbon-based materials may include graphite, carbon nanotubes, non-graphitizable carbon (hard carbon), easily graphitizable carbon (soft carbon), low-temperature sintered carbon, etc. Metal-based materials may include lithium-based materials, aluminum-based materials, silicon-based materials, tin-based materials, etc.

[0046] The negative electrode active material 23 is preferably present in an amount of 2 mg / cm2 relative to the surface area of ​​the negative electrode current collector 21. 2 ~10mg / cm 2 If the filling amount of the negative electrode active material 23 is too small, it tends to be difficult to maintain a high energy density, and even if the filling amount of the negative electrode active material 23 is too large, it is difficult to contribute to the improvement of characteristics.

[0047] The negative electrode active material 23 may be filled in the negative electrode current collector 21 as a negative electrode mixture containing a binder. The binder may be a known binder, for example, a fluorocarbon resin material, etc. In addition, the negative electrode mixture may contain a conductive auxiliary agent as needed.

[0048] [Lithium-ion secondary battery] The negative electrode of this embodiment is suitable for use in a lithium ion secondary battery including a negative electrode, a positive electrode, a solid electrolyte, and other battery elements as required. The lithium ion secondary battery can employ known battery elements such as a battery container.

[0049] The solid electrolyte is not particularly limited as long as it is a material that can conduct lithium ions. For example, the solid electrolyte can use a polymer solid electrolyte such as a polyethylene oxide-based polymer compound, a polymer compound containing at least one of a polyorganosiloxane chain or a polyoxyalkylene chain, a sulfide solid electrolyte, an oxide solid electrolyte, and the like.

[0050] The positive electrode can be, for example, a positive electrode having a layer containing a positive electrode active material formed on a positive electrode current collector. The positive electrode active material is not particularly limited, and known materials can be applied. Examples of the positive electrode active material include layered positive electrode active material particles, spinel-type positive electrode active materials, olivine-type positive electrode active materials, and the like. The layer containing the positive electrode active material can contain a binder, a conductive aid, a solid electrolyte, and the like. The binder and the conductive aid are not particularly limited, and binders and conductive aids known as materials for solid-state batteries can be applied.

[0051] [Method for manufacturing negative electrode] The negative electrode of the present embodiment can be manufactured by a manufacturing method including the following steps: a negative electrode active material filling step of filling a negative electrode current collector composed of a metal porous body with a negative electrode active material; and a pore forming step of forming pores in a negative electrode precursor. Other manufacturing steps are not particularly limited, and known methods used as a manufacturing method for solid-state batteries can be applied.

[0052] (Negative Electrode Active Material Filling Step) The method of filling the negative electrode active material into the negative electrode collector is not particularly limited, and a known method can be applied. The filling process can be, for example, a method of applying the negative electrode mixture containing the negative electrode active material to the inside of the voids of the negative electrode collector using a slit coater or the like. The coating of the negative electrode mixture can also be applied by dip coating, plunger slit coating, comma blade coating, blade coating, etc. instead of slit coating. From the viewpoint of easily maintaining a high energy density, the coating amount of the negative electrode active material relative to the negative electrode collector is preferably 2 mg / cm 2 ~10mg / cm 2 The method of this embodiment may further include a drying step of drying the negative electrode current collector after the negative electrode active material filling step. The drying step is preferably performed under conditions of a pressure of 100 MPa to 800 MPa and a drying temperature of 25° C. to 120° C.

[0053] (Hole Forming Step) The hole forming step can be a known method as long as it is a method that can form a hole having the above-mentioned hole diameter and depth in the negative electrode collector. The hole forming step can be, for example, a method of rolling a roller having a predetermined concave and convex surface pressed with a predetermined pressure. By adjusting the shape and depth of the concave and convex provided on the roller and the pressing pressure, a hole having the hole diameter and depth of the present embodiment can be formed. Example

[0054] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.

[0055] [Example 1] As the negative electrode current collector, a 1 mm thick, 98% porosity, and a specific surface area of ​​5800 m 2 / m 3 Copper foam.

[0056] A negative electrode mixture containing silicon (average particle size 5 μm) as a negative electrode active material, acetylene black as a conductive aid, and styrene butadiene rubber (SBR) as a binder was prepared. The prepared negative electrode mixture was coated with a slit coater at a coating amount of 10 mg / cm 2 The negative electrode current collector after filling was dried at 120° C. for 12 hours under vacuum.

[0057] Next, the negative electrode current collector was roll-pressed at a pressure of 500 MPa using a conventional roll press. 2 The negative electrode current collector was rolled with rollers having circular protrusions of 180 μm in diameter at intervals at a pressure of 500 MPa. For the pores formed in the negative electrode current collector after rolling, the average value of the pore diameter and the number of pores within the range of 100 times the observation field of the electron microscope were counted. In addition, the average value of the cross-sectional area in the horizontal direction of the pores was calculated. The measurement results are shown in Table 1 together with the measurement results of the following embodiments and comparative examples.

[0058] [Examples 2 to 4] The interval between the circular protrusions arranged on the roller is 4.6 pieces / cm. 2 (Example 2), 4.1 pieces / cm 2 (Example 3), 2.6 pieces / cm 2 A negative electrode having holes formed therein was produced in the same manner as in Example 1 except for the roller of Example 4.

[0059] [Example 5] In addition to making the pore size in the negative electrode 100 μm and the number of pores 9.2 / cm 2 The battery design was otherwise the same as in Example 1. A roller having circular protrusions with a diameter of 100 μm disposed on the roller was used.

[0060] [Comparative Example 1] The negative electrode current collector obtained by applying the negative electrode mixture and drying it was not subjected to the second roll pressing, and the negative electrode current collector was produced by the same method as in Example 1. In the negative electrode current collector of Comparative Example 1, when observed within the range of the field of view of an electron microscope at 100 times, no pores larger than 500 nm that could be visually identified were observed.

[0061] [Comparative Example 2] The same battery design as in Example 1 was implemented except that the pore diameter in the negative electrode was changed to 200 μm. The diameter of the circular protrusions arranged on the roller was 200 μm, and the interval between the protrusions was 4.7 protrusions / cm. 2 A negative electrode having a hole portion was produced in the same manner as in Example 1 except for the above.

[0062] [Comparative Example 3] The same battery design as in Example 1 was carried out except that the pore diameter in the negative electrode was changed to 80 μm. The diameter of the circular protrusions arranged on the roller was 80 μm, and the interval between the protrusions was 10.8 protrusions / cm. 2 A negative electrode having a hole portion was produced in the same manner as in Example 1 except for the above.

[0063] The processing accuracy and electrode strength of the negative electrodes of the examples and comparative examples prepared above were confirmed by the following measuring methods.

[0064] [Processing accuracy] After the produced negative electrode was cut into a size of 1 cm square with an insulating ceramic knife, it was cut horizontally using an argon beam (intensity: 4 kV, irradiation time: 12 hr, temperature: -60) of a cross-section production device (JEOL, model: IB-19530CP) in a vacuum to confirm the processability. In addition, the cut cross section was observed with an electron microscope to confirm the horizontal cross-sectional shape of the hole and the depth of the hole. In Examples 1 to 5 and Comparative Example 2, a circular cross-sectional shape was observed. In Comparative Example 3, the metal porous body collapsed during cutting, and the cross-sectional shape after processing could not be confirmed. The holes in Examples 1 to 5 are all through holes. The results of processability and the cross-sectional shape, cross-sectional area, and depth of the hole are shown in Table 1. In addition, the ratio of the total volume of the hole to the porosity of the negative electrode collector (total volume of the hole / porosity) is shown in Table 1. The total volume of the hole is the value obtained by calculating the volume of each hole from the average value of the cross-sectional area and depth and multiplying it by the number of holes. The processability was evaluated based on the following criteria. <Evaluation of Processability> ○: Good cutting is possible, and the cross section and shape of the hole after processing can be confirmed. △: The hole was distorted by the argon beam during processing, and the shape of the hole was slightly deformed and could not be clearly confirmed. ×: The porous metal body collapsed during cutting, and cutting could not be performed satisfactorily. The cross-sectional shape after processing could not be confirmed.

[0065] [Electrode strength] The negative electrode prepared in the above manner was bent using a bending tester (MTI, Model EQ-MBT-12-LD) with a mandrel diameter of 32 mm to check for peeling of the negative electrode active material, etc. The results of electrode strength evaluation based on the following criteria are shown in Table 1. <Evaluation of Electrode Strength> ○: No peeling of the negative electrode active material was observed. △: Partial peeling of the active material was observed. ×: In addition to the peeling of the active material, the structure of the electrode collapsed.

[0066] [Manufacturing of lithium-ion secondary batteries] As the positive electrode active material, Li(Ni 0.6 Co 0.2 Mn 0.2 )O2, thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), acetylene black as a conductive aid, styrene-butadiene rubber (SBR) as a binder, and butyl butyrate as a solvent were put into a rotary mixer, stirred at 2000rpm for 3 minutes, and then degassed for 1 minute to prepare a positive electrode mixture. The mass ratio of the positive electrode active material, solid electrolyte, conductive aid and binder is 75:22:3:3. The positive electrode mixture is applied on aluminum foil as a positive electrode collector and heated at 60°C. After heating, roller pressing is performed to obtain a material with a density of 3.1g / cc and a unit area weight of 26mg / cm 2 The positive electrode of the positive electrode mixture layer.

[0067] Next, a zirconium tube with a diameter of 10 mm was used to pressurize thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4) is pressed into powder to obtain a solid electrolyte layer with a diameter of 10 mm. The positive electrode with a diameter of 10 mm and the solid electrolyte layer are press-formed at a molding pressure of 1000 MPa to obtain a laminate of the positive electrode and the solid electrolyte layer (positive electrode-solid electrolyte layer laminate).

[0068] The positive electrode-solid electrolyte layer stack obtained above was bonded to the negative electrode of Example 1 at 60 MPa to produce a lithium ion secondary battery. Lithium ion secondary batteries were also produced using the same manufacturing method for the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3.

[0069] [Charge and discharge test] For the fabricated lithium-ion secondary battery, at a temperature of 60 °C, after CC charging at a rate of 0.05C to 4.3V, after a rest time of 10 minutes, a charge-discharge test was carried out with a cut-off potential of 0.05C and 2.5V. The charge-discharge test started from charging. In Table 1, as the results of the charge-discharge tests of the lithium-ion secondary batteries of each example and comparative example, the evaluation of the state of Li precipitation and the energy density are shown. The state of Li precipitation was evaluated based on the charge-discharge curve according to the following criteria. <Evaluation of Li precipitation> 〇: In the charging curve, no specific change was confirmed. △: In the charging curve, a voltage drop caused by a micro short circuit was confirmed, but charging could be carried out. ×: During charging, a short circuit caused by abnormal Li precipitation occurred, and sufficient charging could not be carried out.

[0070] [Li growth rate during charging at 1C] For the lithium-ion secondary batteries of each example and comparative example, the growth rate was measured when constant current charging was carried out at 1C until the specified capacity of 3 mAh / cm 2 was reached. The growth of lithium was confirmed by microscopic observation and it was determined that lithium was deposited in the pores. As a result of the above measurement, in any of the examples and comparative examples, the growth thickness of lithium per hour, that is, the Li growth rate, was 90 μm / h.

[0071] Figure 3 A graph showing the results of the energy density of the lithium-ion secondary battery of Example 1 with respect to the space rate. Among them, the space rate is the ratio of the total volume of the pores to the porosity of the negative electrode current collector.

[0072] [Table 1]

[0073] As can be seen from Table 1, the energy densities of the lithium-ion secondary batteries of Examples 1 to 5 are all high values exceeding 800 Wh / L. Although the value of the energy density of the lithium-ion secondary battery of Comparative Example 1 is high, due to unstable Li precipitation, abnormal charging occurs during charging and a micro short circuit occurs, and stable charge-discharge cannot be carried out. Therefore, there is a possibility of internal short circuit etc. in the secondary battery of Comparative Example 1. The lithium-ion secondary battery of Comparative Example 2 has a lower energy density compared to Examples 1 to 5. The lithium-ion secondary battery of Comparative Example 3 had an electrode rupture during the charge-discharge test (the energy density could not be measured).

[0074] In addition, from Figure 3It can be seen that if the ratio of the total volume of the pores to the porosity exceeds 8%, the energy density tends to decrease, and if the above ratio exceeds 10%, the energy density tends to decrease significantly. It is believed that if the ratio of the total volume of the pores to the porosity is 8% or less, it is easy to stably maintain a high energy density. Description of Reference Numerals

[0075] 1 Negative electrode 21. Negative electrode current collector 22 Hole 23 Negative electrode active material 31 Solid Electrolyte W Thickness direction R (hole diameter) H (hole) depth

Claims

1. A negative electrode of a solid-state battery, comprising: a negative electrode current collector comprising a porous metal body as a constituent material; and A negative electrode active material is filled in the negative electrode current collector, The negative electrode current collector is provided with a hole portion in the thickness direction from the surface of the solid electrolyte side, and the hole portion does not have a metal porous body. The pore size of the pore portion is 100 μm to 180 μm.

2. The negative electrode of the solid-state battery according to claim 1, wherein: The ratio of the total volume of the pores to the porosity of the porous metal body, that is, total volume of pores / porosity, is 10 vol% or less.

3. The negative electrode of the solid-state battery according to claim 1, wherein: The ratio of the total volume of the pores to the porosity of the porous metal body, that is, total volume of pores / porosity, is 8 vol% or less.

4. The negative electrode of the solid-state battery according to claim 1, wherein: The depth of the hole in the thickness direction is 3 μm or more.

5. The negative electrode of the solid-state battery according to claim 1, wherein: The depth of the hole in the thickness direction is 5 μm or more.

6. The negative electrode of the solid-state battery according to claim 1, wherein: The hole portion is a through hole.

7. The negative electrode of the solid-state battery according to claim 1, wherein: The cross-sectional shape of the hole is circular or quadrilateral.

8. The negative electrode of the solid-state battery according to claim 1, wherein: The negative electrode active material is a silicon-based material. 9 . A solid-state battery comprising the negative electrode according to claim 1 .